ASUHAN KEBIDANAN PADA Ny. “A” MASA HAMIL, PERSALINAN, MASA NIFAS, NEONATUS, DAN KELUARGA BERENCANA DI UPT PUSKESMAS SOOKO MOJOKERTO - Sulis Diana, M.Kes; Nanda Putri Intan Lesari (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
The Maternal Mortality Rate in Indonesia is still high. The maternal mortality rate in Indonesia stands at 305 per 100,000 live births while the infant mortality rate is at 23 per 1000 live births. The existence of comprehensive monitoring through Continuity of care (COC) is expected to reduce maternal And infant mortality as small as possible. Comprehensive services, which were complete services, starting from the period of pregnancy, parturition, post partum, neonatal, and family planning, were carried out with midwifery management and SOAP documentation. Midwifery care was given to Mrs “A”G1P000. 38 weeks of gestational age were done at the Puskesmas Sooko working area on February 25-May 16 2019. The results of midwifery care performed on Mrs